Tumor targeting dual stimuli responsive controllable release nanoplatform based on DNA-conjugated reduced graphene oxide for chemo-photothermal synergetic cancer therapy. Issue 26 (21st June 2018) - Jiang, Wenjing; Mo, Fan; Lin, Yaohui; Wang, Xusheng; Xu, LiangJun; Fu, FengFu
Abstract : A tumor targeting dual stimuli responsive controllable release drug delivery nanoplatform was fabricated for chemo-photothermal synergetic cancer therapy based on DNA-conjugated reduced graphene oxide. Abstract : In this research, a novel tumor targeting dual stimuli responsive nanoplatform was fabricated for the controllable delivery and release of a drug to realize chemo-photothermal synergetic cancer therapy by integrating a DNA aptamer with polydopamine reduced graphene oxide (rGO-PDA) nanosheets. The rGO-PDA nanosheets simultaneously acted as a near-infrared radiation (NIR) photothermal agent to generate hyperthermia for photothermal therapy and a nano-carrier for loading doxorubicin (DOX), and the specially designed DNA aptamer served as a supplementary carrier for DOX loading as well as targeting moiety/gatekeeper for specific cellular recognition and controllable release of DOX. The proposed nanoplatform possessed a good targeting ability, remarkable photothermal conversion ability and intelligent drug release with both pH and photothermal heating dual stimuli response. The nanoplatform was successfully used to selectively deliver DOX to protein tyrosine kinase 7 over-expressing cancer cells with a loading capacity of 1.56 mg mg −1 and controllable drug release, which responded to both acidic intracellular environments and NIR irradiation. The combination of the dual stimuli responsive controllable release and the dual nanocarrier for drug loading results in efficient chemo-photothermal synergetic therapy and holds great potential for multimodal cancer therapy.